2016
DOI: 10.1097/mcc.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy during cardiopulmonary resuscitation and after restoration of spontaneous circulation

Lars Wik

Abstract: Near-infrared spectroscopy and rSO2 have been used as a monitor during CPR, detection of ROSC, after ROSC, and during post-resuscitation care. Prospective, controlled, randomized clinical studies are needed to document their wide use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Probes may also be influenced by ambient light. [58] J o u r n a l P r e -p r o o f Finally, the value of cerebral oxygen saturation for the prognostication on neurological outcome after CA is at early stage of research, and it could not be properly analysed. More studies are warranted to understand the relationship between initial and overall values of cerebral oxygen saturation with neurological outcome after CA.…”
Section: Limitationsmentioning
confidence: 99%
“…Probes may also be influenced by ambient light. [58] J o u r n a l P r e -p r o o f Finally, the value of cerebral oxygen saturation for the prognostication on neurological outcome after CA is at early stage of research, and it could not be properly analysed. More studies are warranted to understand the relationship between initial and overall values of cerebral oxygen saturation with neurological outcome after CA.…”
Section: Limitationsmentioning
confidence: 99%
“…In contrast to pulse oximetry, NIRS can measure tissue oxygenation in the absence of pulsatile flow, without the need to interrupt chest compressions ( 55 , 57 , 62 ). Since NIRS values are affected by ambient light ( 52 , 77 ), some devices cannot be used outside. Nonetheless, rSO 2 monitoring may aid in the early detection of ROSC and re-arrest in patients with CA ( 55 – 57 , 62 ).…”
Section: Use Of Nirs For Earlier Detection Of Re-arrest In Prehospitamentioning
confidence: 99%
“…As NIRS measures the oxygen saturation in all vessels <1 mm diameter (including arteries, capillaries and venules) (26), it can provide readings in instances of low blood flow, independently of pulsatile flow, including the flow exhibited during cardiac arrest. Its prognostic value has been validated in recent studies (5,27). NIRS could offer a large clinical benefit in that it alerts clinicians promptly, enabling implementation of corrective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cerebral blood flow might be reduced, regardless of normal blood pressure. Some studies have shown that severe brain damage might cause metabolic depression and hyperemia and that increased S ct O 2 may occur in the very early stage of post-cardiac arrest syndrome (8,27). Therefore, the significance of higher or lower S ct O 2 in the early post-resuscitation phase remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%